1998
DOI: 10.1007/pl00010116
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regeneration of Carbonyl Compounds from Oximes with N-Bromosuccinimide Under Neutral and Mild Conditions

Abstract: N-Bromosuccinimide has been found to be an ef®cient and selective reagent for the mild oxidative cleavage of oximes to yield their corresponding carbonyl compounds in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Bandgar reported a method for the selective regeneration of carbonyl compounds from oximes using NBS under mild conditions. 2066 Reddy also found that oxidative cleavage of oximes can be achieved using NBS in water in the presence of β-cyclodextrin at room temperature to generate the corresponding carbonyl compounds (Scheme 756). 2067 We also found that TsNBr 2 can be used for the oxidative deprotection of oximes to the corresponding carbonyl compounds.…”
Section: Protection and Deprotection Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bandgar reported a method for the selective regeneration of carbonyl compounds from oximes using NBS under mild conditions. 2066 Reddy also found that oxidative cleavage of oximes can be achieved using NBS in water in the presence of β-cyclodextrin at room temperature to generate the corresponding carbonyl compounds (Scheme 756). 2067 We also found that TsNBr 2 can be used for the oxidative deprotection of oximes to the corresponding carbonyl compounds.…”
Section: Protection and Deprotection Reactionsmentioning
confidence: 99%
“…The conversion of different oximes to the corresponding carbonyl compounds is a well-known reaction. Bandgar reported a method for the selective regeneration of carbonyl compounds from oximes using NBS under mild conditions . Reddy also found that oxidative cleavage of oximes can be achieved using NBS in water in the presence of β-cyclodextrin at room temperature to generate the corresponding carbonyl compounds (Scheme ).…”
Section: Protection and Deprotection Reactionsmentioning
confidence: 99%
“…The oxidation of oximes with nitrous acid in solutions is a long known procedure for the recovery of aldehydes and ketones from the parent oximes. , Although the mechanism of the reaction was studied very extensively prior to the 1990s , its stoichiometry is still not well-defined and the nature of intermediates is only partly understood. The recent, growing interest in regeneration of carbonyl compounds from stable and readily prepared oximes is due to increasing synthetic importance of this method for carbonyls production. It is desirable to develop a method that is environmentally benign and can be applied to a wide range of aldoximes and ketoximes with high selectivity and easy product isolation.…”
Section: Introductionmentioning
confidence: 99%
“…283 Αναγέννηση των μητρικών καρβονυλικών ενώσεων επιτυγχάνεται και με επίδραση Ν-βρωμο-σουκκινιμιδίου (ΝΒS) σε οξίμες, κάτω από ήπιες συνθήκες και σε πολύ καλές αποδόσεις. 284 Επίσης, οι οξίμες σχηματίζουν υδροξυλαμίνες κατά την κατεργασία τους με οργανομαγνησιακές ενώσεις. 285 Με επίδραση υδραζίνης σε αιθανόλη και εφαρμογή θέρμανσης, οι οξίμες μετατρέπονται σε υδραζόνες, σε πολύ καλές αποδόσεις.…”
Section: άλλες αντιδράσειςunclassified